2019
DOI: 10.1051/matecconf/201925804006
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of shear capacity for precast segmental box girder dry joints by steel fiber and glass fiber

Abstract: The use of precast segmental box girders in the bridge construction projects yields many benefits: economy, high quality, rapid construction, and minimal disruption to site. Previously, precast segments are connected together by epoxy joints. Epoxy fills in the gaps and makes strong connection, but it takes time and effort in the construction process. Later, dry joints have been introduced in the process, and hence the construction could be done much faster. However, there exists some drawback in using the dry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…To simulate the transfer of prestressing force from tendon to concrete member, the confining stress of 1 MPa was applied constantly throughout. The use of the confining stress of 1 MPa is consistent with the experiments conducted in the literatures [9,26,27]. Furthermore, the confining stress of 1 MPa is the upper bound value applied as transferred posttensioning stress in adjacent box girder bridges [28,29].…”
Section: Test Setup and Instrumentationsupporting
confidence: 73%
“…To simulate the transfer of prestressing force from tendon to concrete member, the confining stress of 1 MPa was applied constantly throughout. The use of the confining stress of 1 MPa is consistent with the experiments conducted in the literatures [9,26,27]. Furthermore, the confining stress of 1 MPa is the upper bound value applied as transferred posttensioning stress in adjacent box girder bridges [28,29].…”
Section: Test Setup and Instrumentationsupporting
confidence: 73%
“…Despite such finding, after attaining the maximum load, the capacity of the conventional concrete joints is generally accepted to quickly drop off with only residual forces remaining to carry the load. The failure of the dry joints under direct shear loading always results in brittle fracture along the root of the keys 3,12–15 . Furthermore, the failure of the epoxied joints always occurs in the concrete adjacent to the epoxy layer, on the epoxy layer, or bonding layer between concrete and epoxy 1–3,16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…The failure of the dry joints under direct shear loading always results in brittle fracture along the root of the keys. 3,[12][13][14][15] Furthermore, the failure of the epoxied joints always occurs in the concrete adjacent to the epoxy layer, on the epoxy layer, or bonding layer between concrete and epoxy. [1][2][3]16,17 Thus, to improve the shear capacity, load-transmission, practical construction, and ductility of joints, numerous studies have been conducted on the mechanical behavior of joints with new materials or new types.…”
Section: Introductionmentioning
confidence: 99%
“…e experimental results of Smittakor et al [10] showed that steel fiber could improve the shear resistance of concrete keyed joints. Gopal et al [11] found that the shear bearing capacity of ultra-high-performance fiber reinforced concrete (UHPFRC) key joints increased significantly with the number of keys.…”
Section: Introductionmentioning
confidence: 99%